Flexural Behaviour of RC Beams with a Circular Opening at the Flexural Zone and Shear Zone Strengthened Using Steel Plates - J. Branesh Robert; R. Angeline Prabhavathy; P. S. Joanna; S. Christopher Ezhil Singh; Sivaraj Murugan; S. Rajkumar; Shubham Sharma (Advances in Civil Engineering)
In this paper, an investigation on the behaviour of RC beams with circular openings in the flexural zone and shear zone strengthened using steel plates is presented. Totally seven beams were cast: a control beam, one beam with a circular opening of size of one-third the depth of the beam (100 mmϕ) in the flexural zone, one beam with opening strengthened using the steel plate, one beam with a circular opening of size of 100 mmϕ in the shear zone, one beam with an opening in the shear zone strengthened using the steel plate, one beam with two circular openings of size of 100 mmϕ in the shear zone, and another beam with two openings in the shear zone strengthened using the steel plate. The experiments were conducted in a loading frame of 400 kN capacity. The beams were subjected to two-point loading. The ultimate load carrying capacity reduced marginally by 1.78% and 2.8% compared to that of the control beam when a circular opening of 100 mmϕ was provided in the flexural zone and shear zone, respectively, and when the opening was strengthened with steel plates, it reduced by 3.04% and 25%, respectively, but the ductility increased when steel plates were provided. Beams with an opening of size of one-third the depth of the beam (100 mmϕ) in the flexural zone strengthened with the steel plate can be provided, as the load carrying capacity is only marginally reduced compared to the control beam, and the ductility is more when compared with beams with unstrengthened openings.